Ex vivo study of hematopoiesis in protein malnutrition: characterization of bone marrow stromal cells in mice - Santos, Ed Wilson; Dias, Carolina; Oliveira, Dalila Cunha de; Hastreiter, Araceli; Silva, Graziela Batista da; Beltran, Jackeline Soares de Oliveira; Paredes-Gamero, Edgar Julian; Borelli, Primavera (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
Protein Malnutrition (PM) can promotes the modification of hematopoietic tissue, with changes of extracellular matrix components, affecting the evolution of the cell cycle of hemopoietic cells, reducing the production of precursors and hematopoietic cells both in erythroid series and in the number of leukocytes, leading to anemia and leukopenia. In view of these events, it was hypothetised that changes can occur in the formation and establishment of bone marrow stroma, as well as in cells proliferation, differentiation and maturation, resulting in the change in the microenvironment inducing hemopoese, affecting signaling cellular processes and the physiology of stem and progenitor cells